Inheriting and Developing of Tai Lue Singing Participation in Chiang Kham, Phayao Province - et. al., Rattana Tapang, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Inheriting and developing of Tai Lue singing participation in Chiang Kham, Phayao province Thailand was a research article from the Model of Cultural Innovation of a Tai Lue Singing Cultural Identity at Chiangkham District Phayao Province Project of the University of Phayao. The purposes of this study were 1) to create inheritance and development process of Tai Lue singing participation 2) to create Tai Lue singing innovation. Moreover, the engagement focuses in building innovation and innovators of Tai Lue singing by the singers that can utilize knowledge to create Tai Lue singing by driving in producing more community innovators to use these processes to develop the further performance. The study was found that 1) the process in creating innovation of Tai Lue singing was that all singers could conduct the participation cooperatively, 2) the innovation of two songs of Tai Lue were including Pleng Aew Muang Phayao Muan Jai (Travelling in Phayao Happily Song) and Pleng Tam Nan Sueb San Tai Lue (Inheriting Tai Lue Legend Song). However, the traditional songs of Tai Lue singing were recorded namely Khab Pa, Khab Bao Tor Sao which are about flirting between men and women. Lastly, the community innovators under the participation could create the same purposes and promote unity, love, happiness, pride and also the values of Tai Lue singing by using Tai Lue Songs as the main materials to build Tai Lue ethic which influences to create creative process to increase more values in the culture of Tai Lue singing for ethics.